Fertility treatment increases the risk of preterm birth independent of multiple gestations - David C. Fineman; Roberta L. Keller, M.D; Emin Maltepe, M.D; Paolo F. Rinaudo, M.D; Martina A. Steurer, M.D (Elsevier, 2023)
Objective: To investigate the complex interplay between fertility treatment, multiple gestations, and prematurity. Design: Retrospective cohort study linking the national Center for Disease Control and Prevention infant birth and death data from 2014 to 2018. Setting: National database from Center of Disease Control and Prevention. Patients: In total, 19,454,155 live-born infants with gestational ages 22-44 weeks, 114,645 infants born using non IVF fertility treatment (NIFT), and 179,960 via assisted reproductive technology (ART). Intervention: Noninvasive fertility treatment or ART vs. spontaneously conceived pregnancies. Main Outcome Measures: The main outcome assessed was prematurity. Formal mediation analysis was conducted to calculate the percentage mediated by multiple gestations. Results: Newborns born using NIFT or ART compared with those with no fertility treatment had a higher incidence of multiple gestation (no fertility treatment = 3.0%; NIFT = 24.7%; ART = 32.7%; P<.001) and prematurity (no fertility treatment = 11.2%; NIFT = 23.4%; ART = 28.4%; P<.001). Mediation analysis demonstrates that 76.8% (95% confidence interval [CI], 75.2%-78.1%) of the effect of NIFT on prematurity was mediated through multiple gestations. Similarly, 71.2% (95% CI, 70.8%-72.7%) of the effect of ART on prematurity is mediated through multiple gestation. However, the direct effect of NIFT on prematurity is 20.4% (95% CI, 19.0%-22.0%). The direct effect of ART was 24.7% (95% CI, 23.7%-25.6%). Conclusion: A significant proportion of prematurity associated with fertility treatment is mediated by the treatment itself, independent of multiple gestations.